The Tyrosine Kinase-Driven Networks of Novel Long Non-coding RNAs and Their Molecular Targets in Myeloproliferative Neoplasms - Wong, Nonthaphat Kent; Luo, Shumeng; Chow, Eudora Y. D.; Meng, Fei; Adesanya, Adenike; Sun, Jiahong; Ma, Herman M. H.; Jin, Wenfei; Li, Wan-Chun; Yip, Shea Ping; Huang, Chien-Ling (Frontiers in Cell and Developmental Biology, 2021)
Recent research has focused on the mechanisms by which long non-coding RNAs (lncRNAs) modulate diverse cellular processes such as tumorigenesis. However, the functional characteristics of these non-coding elements in the genome are poorly understood at present. In this study, we have explored several mechanisms that involve the novel lncRNA and microRNA (miRNA) axis participating in modulation of drug response and the tumor microenvironment of myeloproliferative neoplasms (MPNs). We identified novel lncRNAs via mRNA sequencing that was applied to leukemic cell lines derived from BCR-ABL1-positive and JAK2-mutant MPNs under treatment with therapeutic tyrosine kinase inhibitors (TKI). The expression and sequence of novel LNC000093 were further validated in both leukemic cells and normal primary and pluripotent cells isolated from human blood, including samples from patients with chronic myelogenous leukemia (CML). Downregulation of LNC000093 was validated in TKI-resistant CML while a converse expression pattern was observed in blood cells isolated from TKI-sensitive CML cases. In addition to BCR-ABL1-positive CML cells, the driver mutation JAK2-V617F-regulated lncRNA BANCR axis was further identified in BCR-ABL1-negative MPNs. Further genome-wide validation using MPN patient specimens identified 23 unique copy number variants including the 7 differentially expressed lncRNAs from our database. The newly identified LNC000093 served as a competitive endogenous RNA for miR-675-5p and reversed the imatinib resistance in CML cells through regulating RUNX1 expression. The extrinsic function of LNC000093 in exosomal H19/miR-675-induced modulation for the microenvironment was also determined with significant effect on VEGF expression.